Oxidation Behaviour of Amorphous Steel: Impact on Electromagnetic Properties - Monsalve-Gonzalez, A; Artigas-Abuin, A (Emerald Group Publishing Ltd., 2017)
Purpose: High silicon amorphous steels are gaining preference as the material of choice for the fabrication of the core of low and medium power electrical transformers because they present a better electromagnetic behaviour compared to that offered by common grain-oriented and non-oriented high silicon steels. This study aims to investigate the effects that the environmental conditions present during the high temperature annealing of cores exert on the surface oxidation and electromagnetic changes experienced by a commercial amorphous steel alloy. Design/methodology/approach: The effect of environmental impact on the correct development of annealing practices during the manufacture process of amorphous steel cores used in distribution transformers was studied by the development of an oxidation reactor. With this installation, it was possible to simulate environmental conditions that could affect the surface of magnetic cores made from amorphous steel. Findings: It was found that: the surface oxidation of amorphous steels affects their electromagnetic behaviour, environmentally induced surface degradation can be modelled at laboratory scale and oxide formation does not affect the amorphous condition of the alloy. Originality/value: The effect of surface oxidation induced by the existence of water vapour in the annealing process of cores made from amorphous steels and its impact on the electromagnetic behavior of these alloys has been barely studied. © Emerald Publishing Limited.